Behavioral Feeding Circuit: Dietary Fat-Induced Effects of Inflammatory Mediators in the Hypothalamus - Poon, Kinning (Frontiers in Endocrinology, 2020)
Excessive dietary fat intake has extensive impacts on several physiological systems and can lead to metabolic and nonmetabolic disease. In animal models of ingestion, exposure to a high fat diet during pregnancy predisposes offspring to increase intake of dietary fat and causes increase in weight gain that can lead to obesity, and without intervention these physiological and behavioral consequences can persist for several generations. The hypothalamus is a region of the brain that responds to physiological hunger and fullness and contains orexigenic neuropeptide systems that have long been associated with dietary fat intake. The past fifteen years of research show that prenatal exposure to a high fat diet increases neurogenesis of these neuropeptide systems in offspring brain and are correlated to behavioral changes that induce a pro-consummatory and obesogenic phenotype. Current research has uncovered several potential molecular mechanisms by which excessive dietary fat alters the hypothalamus and involve dietary fatty acids, the immune system, gut microbiota, and transcriptional and epigenetic changes. This review will examine the current knowledge of dietary fat-associated changes in the hypothalamus and the potential pathways involved in modifying the development of orexigenic peptide neurons that lead to changes in ingestive behavior, with a special emphasis on inflammation by chemokines.